Chimeric Antigen Receptor T-Cell Therapeutics for Multiple Myeloma: Moving Into the Spotlight. Issue 3 (May 2021) - Wang, Bo; Rajeeve, Sridevi; Madduri, Deepu
Abstract : Abstract: Chimeric antigen receptor (CAR) T-cell therapy has quickly emerged as a highly promising treatment for patients with relapsed and refractory multiple myeloma. There are numerous candidates under development, each with their unique characteristics and points of differentiation. The most recent US Food and Drug Administration approval of the first B-cell maturation antigen–targeted CAR-T cell therapy on March 26, 2021, has paved a path forward for the eventual evaluation of more of these investigational agents undergoing clinical trials. Herein, we highlight, from a clinical development perspective, the CAR-T cell therapies farthest along in development with updated data from the American Society of Hematology 2020 annual meeting. We also discuss potential paths of overcoming resistance to these therapies and the future direction for CAR-T cell therapeutics in multiple myeloma.